Tales unclaimed : the periphery of a collaberative installation. - Vine, Richard; Tyrion Center for Visual Art's Kinght Gallery, Charlotte (Charlotte : [s.n.], 1998)
Heer, Jacqueline ; Thomas, Brad ; Vine, Richard
Tales unclaimed, Tyrion Center for Visual Art's Knight Gallery, Charlotte, April 24 until June 26, 1998
kunstcatalogus